Pengaruh Keterlibatan Belajar Matematika terhadap Prestasi Belajar Matematika Siswa SMA Negeri 22 Kabupaten Gowa - Muhammad Awal Nur (Jurnal Equation: Teori dan Penelitian Pendidikan Matematika, 2022)
This study aims to determine how much influence the Engagement of learning mathematics has on the mathematics learning achievement of students at SMA Negeri 22 Gowa Regency. The research method used is ex-post facto quantitative research which is causal. The population in this study were students of class XI SMA Negeri 22 Gowa with a total sample of 207 students. Data collection was carried out using instruments in the form of a learning engagement scale and report cards for the 2020/2021 academic year in mathematics. The data analysis technique used in this study is inferential statistics using simple regression analysis with prerequisite tests including normality tests, linearity tests. Based on the results of the study, it shows that there is a positive and significant influence between the Engagement of learning mathematics and learning achievement of students in SMA Negeri 22 Gowa Regency. This is proven by the value of t count = 4.113 with t table = 0.6757 and sig = 0.000 < = 0.05. It can be concluded that there is a positive and significant effect of Engagement learning mathematics on mathematics learning achievement. The magnitude of the influence of mathematics learning Engagement on mathematics learning achievement is 7.62%.